Geospatial Distribution of Fluoride and Iron in Natural Water Sources in Mangalore City - Kushalan, Sharanya; Kashyap, Anusha; Morajkar, Shaiesh; Hegde, Smitha (Journal of Health and Allied Sciences NU, 2023)
Water is the most essential substance that supports life on earth. Animals and plants require water for their survival. Since water is being lost or used by our body, it is essential to replace it constantly. Humans need clean, potable water for consumption and to meet their daily hygiene needs. However, increased anthropogenic activities have caused a drastic increase in heavy metals in fresh waters. Heavy metals interfere with the normal physiology of the human body. It binds to cellular components, leading to dysfunction of the metabolic processes in our body. This study was undertaken to study the geospatial distribution of selected heavy metals in open-well waters within Mangalore City Corporation limits. Mangalore is perched strategically on the path of rapid development, heading toward becoming a smart city in India. Water samples were collected from all 60 wards in the jurisdiction of Mangalore City Corporation. The fluoride concentration was estimated using the spectrophotometric method using the Sodium 2-(parasulfophenylazo)-1,8-dihydroxy3,6-naphthalene disulfonate (SPADNS) reagent. Similarly, iron was estimated using the phenanthroline reagent. The findings report that the pH of the samples was acidic in 20 wards. Panambur, Kunjathbail North, Mannagudda, Court and Cantonment water was colored. Kunjathbail (North), Kunjathbail (South), Kambala, Kadri North, Bendoor, Bolar, Mannagudda, and Markada, showed high turbidity levels. The fluoride concentration in the samples collected from 60 wards of Mangalore city was less than 1.5 ppm, which is the permissible limit by the World Health Organization. Iron is within the permissible limit except for the wards Court and Boloor, which showed an iron concentration of 0.4 ppm and 3.08 ppm, respectively. However, arsenic was not detected in any of the 180 samples collected from the 60 wards of Mangalore City Corporation.
Keywords: geospatial distribution; well water; fluoride; iron; arsenic; pH; color; turbidity; Mangalore city